PENGARUH PENDAPATAN ASURANSI TERHADAP PENDAPATAN INVESTASI PADA PERUSAHAAN ASURANSI JIWA DI INDONESIA PERIODE 2014-2018 - Ratu Humaemah; Indah Yani (UIN Sultan Maulana Hasanuddin Banten, 2019)
Abstract Sharia financing and investment activities in principle are activities carried out by property owners (Investors) towards business owners (Issuers) to empower business owners in conducting their business activities where the owner of assets (Investors) hopes to obtain certain benefits. Therefore, financing and financial investment activities are basically the same as other business activities, namely maintaining the principle of halal and fairness. The financial data shown in the table shows that insurance income and investment income in life insurance companies in Indonesia from 2014 to 2018 experienced fluctuating developments. The purpose of this study is to determine whether there is an influence of insurance income on investment income in Islamic life insurance companies in Indonesia. The method used in this study is a quantitative method that uses a classic assumption test, hypothesis testing, and the coefficient of determination test. The data used are secondary data obtained by the official website of a life insurance company. The results showed that the independent variable of insurance income had a significant effect on investment income, this result was seen from the tcount of 8,450 while the ttable obtained from the distribution table t was sought at the significance of 5%: 2 = 2.5% (two-way test) degrees of freedom (df) nk-1 or 30-1-1 = 28 we get t table of 2.04841. because tcount> t table = 8.450> 2.04841 with a significant level of 0.000, because the significant value is smaller than 0.050, it can be concluded that Ha is accepted. This means that insurance income has a positive effect on investment income. From testing the coefficient of determination of 0.708 = 70.8% means that insurance income can explain the effect on investment income of 70.8% and the remaining 29.2% is influenced by other variables not discussed in this study.